2020
DOI: 10.1029/2019jd032326
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Polydisperse Sea Spray Size Distributions on Model Predictions of Air‐Sea Heat Fluxes

Abstract: We improved the overestimation issue in bulk model for the total heat flux by con-8 sidering spray timescales. 9 • Using the volume-weighted mean size as a representative size could simplify the 10 quantifying of air-sea fluxes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Ocean spray is composed of small liquid droplets formed through two main pathways (Veron, 2015): the spume drops, produced from the tearing of breaking wave crests by strong winds (Ortiz‐Suslow et al., 2016; Troitskaya et al., 2018; Veron et al., 2012) and bubble bursting, itself decomposed into the film and jet drops production (Cipriano et al., 1983; Ghabache et al., 2014; Lhuissier & Villermaux, 2012; Spiel, 1997). These droplets transport water, heat, dissolved gases, salts, surfactants, and biological materials between the ocean and the atmosphere and these air‐sea fluxes are dependent on the drop size distributions (Mueller & Veron, 2014; Peng & Richter, 2020), while their chemical composition is affected by the production mechanisms (Cochran et al., 2017; Wang et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Ocean spray is composed of small liquid droplets formed through two main pathways (Veron, 2015): the spume drops, produced from the tearing of breaking wave crests by strong winds (Ortiz‐Suslow et al., 2016; Troitskaya et al., 2018; Veron et al., 2012) and bubble bursting, itself decomposed into the film and jet drops production (Cipriano et al., 1983; Ghabache et al., 2014; Lhuissier & Villermaux, 2012; Spiel, 1997). These droplets transport water, heat, dissolved gases, salts, surfactants, and biological materials between the ocean and the atmosphere and these air‐sea fluxes are dependent on the drop size distributions (Mueller & Veron, 2014; Peng & Richter, 2020), while their chemical composition is affected by the production mechanisms (Cochran et al., 2017; Wang et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies including Mueller and Veron (2014b) and Peng and Richter (2019) suggested that these assumptions overestimate the total sea spray-mediated flux due to smaller drops rapidly condensing and warming right before reentrance as they approach the sea even if they were able to thermally adjust to nearly their wet-bulb temperature at some point during their flight. Peng and Richter (2020) used Lagrangian particle simulations to look for interactions between drops of different sizes and found that large drops are more heavily concentrated near the bottom of the spray layer and can increase the moist enthalpy of the lower region to further reduce the net enthalpy contribution of small drops. Fairall et al (2009) found that the slope of the waves played an important role in determining whether large drops would spend a significant time aloft.…”
Section: The Enthalpy Fluxmentioning
confidence: 99%
“…Fairall et al (2009) found that the slope of the waves played an important role in determining whether large drops would spend a significant time aloft. Mueller and Veron (2014b), Richter et al (2019), and Peng and Richter (2020) all raised the concern that large drops may not be transported high enough to experience ambient conditions of T a , RH, or U 10 during their flight. One consideration is that most of these studies, with the exception of Mueller and Veron (2014b) who simulated 10-m wind speeds as high as 50 m/s, generally reported results for 10-m wind speeds below the high wind speeds that are primarily of interest in this study; at lower wind speeds, less sea spray is expected to be produced and the ejected spray is not expected to be lofted as high or remain aloft for as long.…”
Section: The Enthalpy Fluxmentioning
confidence: 99%
See 2 more Smart Citations